1998
DOI: 10.1002/jccs.199800018
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents of Neolitsea parvigemma and Neolitsea konishii

Abstract: White prisms (MeUH); mp 233-235 "C; [a): -125' (C = 0.2, CHC13); UV h max/nm 216; iR v (KBr) cm-' 3 120, 1760, 1745, 1220, 890; '1-1 NMR (200 MHz, CDC13) S/ppm 1.02 (3H, s, H-14), 1.63 (IW, m, H-34, 2.03 (3H, s, 2.64(1H,ddd,~=14.1;9.0; 1.3Hz,H-4a),2.88(1H,ddd,J COCHs),2.10 (3H, d , J = 1.2 Ih.Il-13), 2.31 (IH,m, H-3h), = 14.0; 9.0; 9.0 Hz, H-4b). 3.39 (lH, dd, J = 12.0; 1.9 Hz, H-2), 5.86 (174, br.S, N-7),6.01 (113, S, H-10),7.05 (1H, d, J = 1.3 WZ, H-fi), 7.23 (lH, d, J = 1.2 Hz, H-12); I3C NMR (SO MHz, CDC13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Colorless amorphous powder; CD (E max ) (c = 0.001, MeOH) Dq + 65.7 (278), À 106.2 (322); FAB-MS (negative-ion mode) m/z: 385.14 [M À H] À . The NMR data and MS of compound 3 were identical to the published spectral data of roseoside (Chen et al, 1998).…”
Section: Extraction and Purificationsupporting
confidence: 54%
“…Colorless amorphous powder; CD (E max ) (c = 0.001, MeOH) Dq + 65.7 (278), À 106.2 (322); FAB-MS (negative-ion mode) m/z: 385.14 [M À H] À . The NMR data and MS of compound 3 were identical to the published spectral data of roseoside (Chen et al, 1998).…”
Section: Extraction and Purificationsupporting
confidence: 54%
“…5) is an oxoaporphine alkaloid that has been isolated from overground parts of plants belonging to different families such as Annonaceae (Chang et al, 1998;Chen et al, 1996), Lauraceae (Chen et al, 1998), Magnoliaceae (Chen et al, 1976), Fumariaceae (Blanco et al, 1993;Tojo et al, 1991), Menispermaceae (Ohiri et al, 1982) and Papveraceae (Sari, 1999), which is also found widely exist in many traditional Chinese medicine, such as aquilegia ecalcarata Maxim (Ranunculaceae) mainly distributed in Sichuan and Yunnan Provinces of China and used for the treatment of necrotic boils, pustulosis and other infections . The primary screening results reveal that oxoglaucine possesses strong anticancer activity, such as against HCT-8 (ED 50 = 1.00 µg/ml) and K B (ED 50 = 2.00 µg/ml) (Chang et al, 2002;Chen et al, 2002;Wu et al, 1989).…”
Section: Oxoglaucine-metal Based Anticancer Agentsmentioning
confidence: 99%
“…The primary screening results reveal that oxoglaucine possesses strong anticancer activity, such as against HCT-8 (ED 50 = 1.00 µg/ml) and K B (ED 50 = 2.00 µg/ml) (Chang et al, 2002;Chen et al, 2002;Wu et al, 1989). In addition, oxoglaucine exhibits other important pharmacological activities including antiplatelet aggregation (Chang et al, 1998;Jantan et al, 2006), immunomodulatory activity (Ivanovska et al, 1997 and2000), treatment of adjuvant arthritis , antiinflammatory (Remichkova et al, 2009), antifungal activity (Clark et al, 1987). Fig.…”
Section: Oxoglaucine-metal Based Anticancer Agentsmentioning
confidence: 99%
“…Thus, the structure of compound 2 was established as 4'-(hydroxy(12-(3-hydroxy-4,6,7-trimethoxyphenanthren-1-yl)ethyl)amino)cyclopenta-1',3'-dienecarbaldehyde, and given a trivial name of beilschglabrine B. The known compounds, lupeol (Yang et al, 2009), taraxerol (Chen et al 1998) and 24-methylenelanosta-7,9-diene-3β-15α-diol (Lue et al, 1998), were identified by comparison of their spectroscopic data with published data.…”
mentioning
confidence: 99%